Toxoplasma gondii Induces Granulocyte Colony-Stimulating Factor and Granulocyte-Macrophage Colony-Stimulating Factor Secretion by Human Fibroblasts: Implications for Neutrophil Apoptosis - Channon, Jacqueline Y. (American Society for Microbiology, 2002)
Human neutrophils are rescued from apoptosis following incubation with once-washed, fibroblast-derived Toxoplasma gondii tachyzoites. Both infected and uninfected neutrophils are rescued, implicating a soluble mediator. In this study we investigated the origin and identity of this soluble mediator. Neutrophils were incubated either with purified tachyzoites or with conditioned medium derived from T. gondii-infected human fibroblasts. Conditioned medium was found to be a potent stimulus that delayed neutrophil apoptosis up to 72 h, whereas purified and extensively washed tachyzoites had no effect. Delayed apoptosis correlated with up-regulation of the neutrophil antiapoptotic protein, Mcl-1, and the neutrophil interleukin 3 receptor α subunit (IL-3Rα), suggesting a role for granulocyte-macrophage colony-stimulating factor (GM-CSF). GM-CSF and granulocyte colony-stimulating factor (G-CSF) were measurable in conditioned medium by enzyme-linked immunosorbent assay. Neutralizing antibodies to GM-CSF and G-CSF were additive in abrogating delayed neutrophil apoptosis induced by conditioned medium. Inhibitors of Src family tyrosine kinases, G(i) proteins, phosphatidylinositol 3-kinase, p44(erk1) and p42(erk2) mitogen-activated protein kinases, and Jak2 kinases partially attenuated the effect of conditioned medium, consistent with a role for G-CSF and/or GM-CSF. Hence, delayed neutrophil apoptosis is mediated by GM-CSF and G-CSF secreted by T. gondii-infected human fibroblasts. This enhanced neutrophil survival may contribute to the robust proinflammatory response elicited in the T. gondii-infected host.